2010
DOI: 10.1038/onc.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside synthase knockout in oncogene-transformed fibroblasts depletes gangliosides and impairs tumor growth

Abstract: Biologically active membrane gangliosides, expressed and released by many human tumors, are hypothesized to significantly impact tumor progression. Lack of a model of complete and specific tumor ganglioside depletion in vivo, however, has hampered elucidation of their role. Here we report the creation of a novel, stable, genetically induced tumor cell system resulting in specific and complete blockade of ganglioside synthesis. Wild type (WT) and GM3 synthase/GM2 synthase double knockout (DKO) murine embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…It is noteworthy that knockout of ganglioside synthase, which affects lipid raft composition, reduced migration of normal human fibroblasts (Liu et al 2010), and immunotherapy with anti-GD2 mAbs results in long term survival of patients with neuroblastoma (Ahmed and Cheung 2014). In the present study, we found that knocking down ST6GalNAcVI mRNA expression reduced the effect of DSGb5 on RCC cells; therefore, DSGb5 represents a potential anti-tumor treatment target for RCC patients.…”
Section: Discussionsupporting
confidence: 57%
“…It is noteworthy that knockout of ganglioside synthase, which affects lipid raft composition, reduced migration of normal human fibroblasts (Liu et al 2010), and immunotherapy with anti-GD2 mAbs results in long term survival of patients with neuroblastoma (Ahmed and Cheung 2014). In the present study, we found that knocking down ST6GalNAcVI mRNA expression reduced the effect of DSGb5 on RCC cells; therefore, DSGb5 represents a potential anti-tumor treatment target for RCC patients.…”
Section: Discussionsupporting
confidence: 57%
“…Immunoprecipitation Experiments-Aliquots of the detergent-resistant membrane fractions obtained from [1][2][3] H]sphingosine-labeled cells were diluted 10-fold in immunoprecipitation buffer (50 mM Tris-HCl, pH 7.4, 150 mM NaCl, 2 mM NaF, 1 mM EDTA, 1 mM EGTA, 1 mM Na 3 VO 4 , 1 mM PMSF, 75 milliunits/ml aprotinin, 1% Triton X-100). After preclearing for nonspecific binding, 10 g/ml anti-caveolin-1 rabbit or 4 g/ml anti-c-Src antibody or normal rabbit IgG (as negative control) was added to the supernatants, and the mixtures were put in rotation overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…However, gangliosides deeply affect tumor cell adhesion, motility, and migration. Ganglioside depletion by double knock-out of GM3 synthase and GM2 synthase in transformed fibroblasts reduced their migration on fibronectin and reduced their tumorigenic potential in syngeneic immunocompetent mice (3). However, transfection with GM1a/GD1b synthase, leading to the expression of complex gangliosides, inhibited neuroblastoma cell migration by affecting the Rho/Rac1 pathway (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Depletion of HEXB via siRNA was found to decrease the angiogenic potential. Another study using GM2 and GM3 synthase double knockout oncogenetransformed fibroblasts in a cancer model in mice found that downregulation of GM1 induces strikingly slower tumor growth (52). Although the precise role of GM2 in cancer progression is still not completely understood, it may prove to be an interesting therapeutic target.…”
Section: Gm1 and Gm2 In Infections Cancer And Insulin Metabolismmentioning
confidence: 99%